2000
DOI: 10.1080/00343400050192847
|View full text |Cite
|
Sign up to set email alerts
|

Mergers/Acquisitions and Restructuring in the EU Chemical Industry: Patterns and Implications

Abstract: CHAPMAN K. and EDMOND H. (2000) Mergers/acquisitions and restructuring in the EU chemical industry: patterns and implications, Reg. Studies 34, 753-767. High levels of merger/acquisition activity, especially international transactions, have been a characteristic of the global economy since the mid - 1980s. A significant proportion of this activity has been focused on the EU where it has been stimulated by economic integration. Research into the phenomenon has been limited by data availability. Information from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…Other studies examined outcomes of spatial influences, including how acquisitions have lead to greater geographic concentration of economic activity (Rodriguez-Pose and Zademach, 2003), facilitated the transfer of corporate control across geographic boundaries (Chapman and Edmond, 2000), and generated social and economic tensions within local communities (Jonas, 1992). Nonetheless, economic and corporate geography research provides a limited understanding about the underlying mechanisms of the spatial evolution of firms (see Maskell, 2001), which this study helps advance.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examined outcomes of spatial influences, including how acquisitions have lead to greater geographic concentration of economic activity (Rodriguez-Pose and Zademach, 2003), facilitated the transfer of corporate control across geographic boundaries (Chapman and Edmond, 2000), and generated social and economic tensions within local communities (Jonas, 1992). Nonetheless, economic and corporate geography research provides a limited understanding about the underlying mechanisms of the spatial evolution of firms (see Maskell, 2001), which this study helps advance.…”
Section: Discussionmentioning
confidence: 99%
“…Green (1990) investigated the US market in the 1970s and 1980s and concluded that the economic centres of a country are key factors in developing the nearby areas. According to this idea, M&As contributed to the increase in corporate control for the urban agglomerations and also to a reinforcement of the existing company headquarters (Chapman & Edmond, 2000). Therefore, cities are considered to be the locations of power and control and with the help of the M&As their power will increase even more .…”
Section: Related Studiesmentioning
confidence: 99%
“…Not all authors, however, share this optimistic vision. Chapman and Edmond (2000) demonstrate that the mergers and acquisitions process within the European chemical industry has led to a systematic transfer of ownership of firms from the south of the continent to northern countries. The restructuring processes that followed then produced fairly clear, negative effects (loss of jobs) on the regions of the firms acquired.…”
Section: Corporate Ownership and Regions: Theoretical Approachesmentioning
confidence: 99%
“…The various links between the firms cannot, therefore, be weighted according to the size of the target firm. Like the work by Chapman and Edmond (2000) on mergers/acquisitions in the EU chemical industry, the analysis will thus simply address the "events", i.e. the number of links between the companies.…”
Section: Datamentioning
confidence: 99%